A Strategy to Improve Social Studies Learning Outcomes of Fifth-Grade Elementary Students through the STAD Model Assisted by TikTok Videos: Strategi Meningkatkan Hasil Belajar IPS Kelas V SD melalui Model STAD Berbantuan Video TikTok - Tsaqila Ziyan Ahda; Nurdinah Hanifah; Ani Nur Aeni (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
This study aimed to improve the learning outcomes of fifth-grade students in Social Studies (IPS), specifically on Indonesian culture, by applying the cooperative learning model Student Teams Achievement Division (STAD) combined with short educational TikTok videos. A Classroom Action Research (CAR) design was conducted in two cycles with 29 students at SDN Rancakasumba 6. Each cycle consisted of planning, implementation, observation, and reflection. Data were collected through observations of teacher and student activities, interviews, learning outcome tests, and documentation. The findings revealed consistent improvements: lesson planning increased from 93.75% in Cycle I to 100% in Cycle II; teacher performance improved from 87.5% to 96%; student activity rose from 48% (14 of 29 students) to 83% (24 of 29 students); and learning mastery increased from 31% at baseline (9 of 29 students) to 52% in Cycle I (15 of 29 students) and 83% in Cycle II (24 of 29 students), exceeding the Minimum Mastery Criterion (80%). These results indicate that integrating the STAD model with short TikTok videos effectively enhances student engagement and academic achievement in Social Studies. However, the study was limited to one class, a two-week duration, and one topic (Indonesian culture), suggesting the need for further replication across different subjects and contexts.